Fishing Among The Marine Nomads Of The Strait Of Magellan Before And During The Occidental Contact Period - Torres Elgueta, Jimena Andrea; Béarez, Philippe; San Roman Bontes, Manuel Julio (My University, 2021)
Since the first half of the 16th century, the Patagonian archipelagos have been the scenery for multiple encounters between European sailors and the indigenous canoeros from this southern region. These contacts were recurrent in the central zone of the Strait of Magellan, and in the course of time the interaction was changing of modality and intensity, adding other cultural agents such as British, North American and Northern Patagonian (chilotes) pinniped hunters, scientific, religious, military and commercial missions. The result of these social dynamics generated irreversible changes in their marine nomadic way of life until today. Within the framework of these expeditions with diverse purposes, ethnographic and chronicle writings were generated that show different areas of the life of the marine nomads in the Strait of Magellan and adjacent seas (the Kawésqar), emphasizing the role of mobility to solve subsistence needs, mainly the collection of molluscs, hunting of birds and marine mammals. Fishing activity, on the other hand, was generally characterized as secondary and with brief descriptions; this contrasts with the accounts of the canoeros groups that inhabited from the south of the Strait of Magellan to Cape Horn (the Yaghans) whose descriptions of fishing and its techniques were recurrent and described in detail. In order to understand the subsistence of the canoeros in the Strait of Magellan in the moments prior to the Occidental contact and to what extent this latter had repercussions on it, this work assesses the role of fishing based on the ichthyo-archaeological evidence and the fishing technology present in archaeological sites after 1,500 years BP. The data are then compared with the information provided by ethnohistorical sources in order to discuss the continuities and changes in this subsistence activity.